DEVELOPMENT OF CONTEXTUAL-BASED CHEMISTRY TEACHING MATERIALS ON THE SUBJECT OF BUFFER SOLUTION IN SENIOR HIGH SCHOOL - Sari, Sri Adelila; Marbun, Catherine Juperta Hotmatua (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
This study was aimed to analyse: (1) Development of contextual-based chemistry teaching materials on the subject of BSNP standardized buffer solutions, (2) Validity of lecturers and chemistry teachers on developed chemistry teaching materials, (3) Improvement of student learning outcomes with the use of contextual-based chemistry teaching materials on the subject of developed buffer solutions. The research method uses RD with ADDIE model.The instruments used are in the form of interview sheets, BSNP standardized teaching material validation sheets, student response questionnaire sheets, and test question instruments as many as 20 valid questions. After being validated, this teaching material was tested to students of class XI IPA 1 SMA N 11 Medan in the 2023/2024. The research results obtained, namely: (1) The development was carried out using the RD method with the ADDIE development model which was adjusted to the BSNP eligibility standards, (2) The results of validation obtained an average value of 3,64 with valid criteria and feasible to use and based on student response questionnaires to teaching materials obtained an average value of 92,23% with very good criteria (3) The results of the N-Gain analysis obtained by 0,33 with a medium category,there is an increase in student learning outcomes.